REDUCING PRODUCTION REJECTS AND DELIVERY DAMAGE THROUGH BPM: A FIBER CEMENT COMPANY CASE STUDY - Gerry Williekumaro; Mohammad Agung Saryatmo (International Journal of Application on Economics and Business, 2025)
This study aims to reduce production rejects and shipping damage in a fiber cement manufacturing company through the implementation of Business Process Management (BPM). The research was conducted at PT XYZ, which has been facing inefficiencies in its production and distribution processes, as indicated by a high percentage of defective products and increasing shipping damage. A qualitative case study approach was used, with data collected through interviews, observations, and company documentation. Analysis was conducted using the Anakonda and 5 Whys methods to identify root causes, which were then used as the basis for designing To-Be business processes using Business Process Model and Notation (BPMN). The implementation results showed that standardization of machine parameters, regular maintenance schedules, and improved packaging and shipping procedures were able to reduce the reject rate to 0.30% (target 0.34%) and damage to 0.05% (target 0.15%). This study concludes that BPM is effective in improving operational efficiency and can serve as a reference for similar companies in implementing sustainable business process improvements.